TRICHILIA EMETICA: ETHNOBOTANICAL SURVEY AND THE ANTITYROSINASE ACTIVITY RESULTS - Komane AM, B.; Viljoen, A. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
African traditional medicine greatly contributes to the cosmetics industry. However scientific data confirming its use in improving post-inflammatory hyperpigmentation is sparse. Trichilia emetica is one of many medicinal plants used for dermatological purposes. Traditionally, the bark is used as part of a skin lightening treatment by Venda people (Limpopo Province). Tyrosinase is a multifunctional copper-containing enzyme that catalyzes tyrosine to form melanin which darkens the skin. In excess the process results in melanogenesis which promotes the formation of hyperpigmentation. An ethnobotanical survey was conducted by interviewing traditional healers and users. Trichilia emetica (methanol extracts, aqueous extracts of the bark and leaves) (20 – 200 Âµg/ml, pH 6.5) were tested in vitro using the colourimetric tyrosinase inhibition assay. Kojic acid and dimethyl sulfoxide were used as positive and negative controls, respectively. The results of the ethnobotanical survey showed that the powdered bark was mixed with lemon juice to reduce hyperpigmentation on the skin. Traditional healers reported that this paste has a skin-lightening effect and this was confirmed by the users of the treatment. The highest percentage inhibition on colourimetric tyrosinase assay was obtained with aqueous extract (12%) which was significantly lower than the positive control (98%). These studies confirmed that T. emetica has potential in reducing post-inflammatory hyperpigmentation, hence validating the use of the plant as a skin depigmenting remedy.